Analysis of Information Literacy Programs in Libraries based on the SCONUL Seven Pillars Model - Isna Fistiyanti (Record and Library Journal, 2023)
Background of the study: This study aims to find out what are the information literacy programs in the UIN library in East Java and whether the information literacy programs meet the SCONUL Seven Pillars information literacy model standards. Purpose: To find out what information literacy programs are and whether these programs meet the SCONUL Seven Pillars information literacy model standards. Method: This study uses a qualitative descriptive approach. The data analysis technique was carried out by observing the selection of informants, collecting data in the form of observations and interviews, followed by the process of analyzing qualitative data up to the interpretation of the data. Findings: The first result, in general, the training programs at UIN are similar, although there is no uniformity in the curriculum. The second result is that of all the pillars of the SCONUL Seven Pillars standard, the UIN Maulana Malik Ibrahim Malang Library has provided all capabilities in the form of information literacy programs to users and the other three libraries have not met these standards. Conclusion: There is no uniformity in the information literacy curriculum at UIN libraries in the East Java region. So that there is a need to improve and hold collaborative information literacy training program curricula.